2015
DOI: 10.3390/v7082831
|View full text |Cite
|
Sign up to set email alerts
|

Mate-Pair Sequencing as a Powerful Clinical Tool for the Characterization of Cancers with a DNA Viral Etiology

Abstract: DNA viruses are known to be associated with a variety of different cancers. Human papillomaviruses (HPV) are a family of viruses and several of its sub-types are classified as high-risk HPVs as they are found to be associated with the development of a number of different cancers. Almost all cervical cancers appear to be driven by HPV infection and HPV is also found in most cancers of the anus and at least half the cancers of the vulva, penis and vagina, and increasingly found in one sub-type of head and neck c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 91 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…can potentially identify smaller deletions (<3 kb) than MPseq based on the design of the array and the library preparation for MPseq. [12][13][14]38 On the other hand, MPseq can profile the whole genome and identify other patterns of chromoanagenesis including chromoplexy. For illustration of the sensitivity of MPseq to identify rearrangements, a recent study only found 43 gene fusions in 22 specimens with RNAseq in comparison to the 1535 rearrangements and 637 gene fusions we identified in the same sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…can potentially identify smaller deletions (<3 kb) than MPseq based on the design of the array and the library preparation for MPseq. [12][13][14]38 On the other hand, MPseq can profile the whole genome and identify other patterns of chromoanagenesis including chromoplexy. For illustration of the sensitivity of MPseq to identify rearrangements, a recent study only found 43 gene fusions in 22 specimens with RNAseq in comparison to the 1535 rearrangements and 637 gene fusions we identified in the same sample size.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Mate-pair sequencing (MPseq) differs from standard NGS approaches by tiling the whole genome with larger fragments (2 to 5 kb) to reliably detect structural variants such as insertions, deletions, and rearrangements. 12 We previously used MPseq to determine the lineage relationships of multifocal lung cancer, to identify a chromoplectic ALK rearrangement in an inflammatory myofibroblastic tumor, to discover recurrent t(6:7)(p25.3;q32.3) translocations in ALK-negative anaplastic large cell lymphomas, and for other purposes. [13][14][15][16][17] Recently, we have also integrated MPseq with RNA sequencing (RNAseq) to identify transcribed chromosomal rearrangements in peripheral T cell lymphomas.…”
Section: Introductionmentioning
confidence: 99%
“…The high throughput genomic mate pair libraries from HMCLs were prepared by the Mayo Clinic Genome Core Facilities using the Illumina Mate Pair protocols and their available kit (Nextera Mate Pair Sample Preparation kit, Illumina) 10,24 , Then, two samples were run on one lane of an Illumina HiSeq2000 with 50 bp reads. The sequences were aligned to hg19 using BWA, and a BAM file containing only the clustered discordant reads with clustered mates was created.…”
Section: Methodsmentioning
confidence: 99%